EQUIVALENCE VERSUS NON-EQUIVALENCE IN ECONOMIC TRANSLATION - Cristina, Chifane (Strategii Manageriale)
This paper aims at highlighting the fact that “equivalence” represents a concept worth revisiting and detailing upon when tackling the translation process of economic texts both from English into Romanian and from Romanian into English. Far from being exhaustive, our analysis will focus upon the problems arising from the lack of equivalence at the word level. Consequently, relevant examples from the economic field will be provided to account for the following types of non-equivalence at word level: culturespecific concepts; the source language concept is not lexicalised in the target language; the source language word is semantically complex; differences in physical and interpersonal perspective; differences in expressive meaning; differences in form; differences in frequency and purpose of using specific forms and the use of loan words in the source text. Likewise, we shall illustrate a number of translation strategies necessary to deal with the afore-mentioned cases of non-equivalence: translation by a more general word (superordinate); translation by a more neutral/less expressive word; translation by cultural substitution; translation using a loan word or loan word plus explanation; translation by paraphrase using a related word; translation by paraphrase using unrelated words; translation by omission and translation by illustration.